COMPARASION PLASTIC BEHAVIOR OF BOX GRIDER BRIDGE WITH MULTIPLE BOX AND CELLULAR BOX CROSS SECTIONS - Yuslinda, Yuslinda; Rani, Cut Meuthia (Fakultas Teknik Universitas Tanjungpura, 2024)
This study compares plastic deformation behavior in box girder bridges with multiple boxes and cellular box cross-sections. The cross-section's shape significantly influences the girder's post-yield behavior despite being designed to have the exact yield moment. Steel's stress-strain relationship undergoes linear behavior until the yield stress is reached, followed by strain hardening. This study aims to assess the impact of strain hardening on the plastic behavior of girder box bridges.Two types of box girder sections, multiple box and cellular box, are designed with equivalent yield moments. The analysis is conducted with and without strain hardening calculations to evaluate plastic moment, inelastic area length, shape factor, and moment-curvature relationship. The design and analysis follow RSNI T-03-2005 standards using SAP 2000 v.15.Results indicate that multiple box sections exhibit more prominent plastic moments and inelastic area lengths than cellular box sections. Strain hardening calculations show significant increases in plastic moments for both section types. Graphical comparisons highlight the differences in moment-curvature relationships between models with and without strain hardening. Understanding the impact of strain hardening on plastic behavior provides valuable insights for designing and assessing box girder bridges, ensuring structural safety and performance under load conditions.